Clinical and Microbiological Aspects of Perinatal Group B Streptococcal Disease – A Review - Allison Riddle; M. D. Silvana B. Carr (Highlights on Medicine and Medical Research Vol. 13, 2021)
Background: Group B streptococci (GBS) continues to be a universal issue in inducing early onset sepsis in newborns. At the moment, the most effective strategy for reducing early-onset neonatal GBS disease is universal maternal screening for recto-vaginal GBS carriage at 35-37 weeks of gestation, combined with intrapartum antibiotic prophylaxis for colonized mothers. It has not shown a reduction in cases of late or late late-onset GBS infection, which tends to be initiated by environmental elements for newborns with prolonged hospital stays and extended contact with hospital staff. There is a concern whether greater antibiotic use in the peripartum period affects the incidence and antibiotic resistance profiles of GBS and other perinatally acquired bacterial infections; this issue remains unclear. Vaccines against GBS may out to be the most effective and long-term preventive option available.